(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Phase formation of carbonated hydroxyapatite in microwave synthesis conditions was investigated. The possibility of phosphateanions selective substitution by carbonate group was shown in that conditions. Obtained compounds were investigated with XRD-analysis and IR-spectroscopy